Farming Mothers’ Perceptions on Exclusive Breastfeeding in Ori-Ade Area, Osun State - R, Ashimolowo Olubunmi; K, Aromolaran Adetayo; G, Akinmoyede Omolola (Asian Journal of Agriculture and Rural Development, 2013)
The study focused on the perception of rural farming mothers on exclusive breastfeeding in Ori-Ade local government area of Osun state. A purposive sampling technique was used to select 120 rural farming mothers. Data was collected through the use of interview guide. Data was analyzed using both descriptive statistical tools (frequency distribution and percentage) and inferential statistical tools (Chi-square and Pearson product moment correlation).The study revealed that most (77.5%) of the respondents were married, average household size was 8 persons and (45.0%) had secondary education. All (100 percent) of the respondents were aware that babies should be breastfed exclusively for at least six months while 61.70 percent practised the method. Most (90%) of the respondents indicated that sensitization could be used to encourage farming mothers to adopt exclusive breastfeeding method and 86.70% sourced their information on exclusive breastfeeding from the hospital. The chi-square result shows that there was significant relationship between farming mothers’ marital status, education and their perception of exclusive breastfeeding practises (χ2 = 0.038, 0.039 at p < 0.05).Conclusively, farming mothers in the study were aware of exclusive breastfeeding but were not totally practising it. Most of them were not well informed about exclusive breastfeeding. It is therefore recommended that rural farming mothers should be enlighten to enrich their knowledge of exclusive breast feeding.